Diagnóstico y tratamiento de la sarna canina - Rivera Abad, Cristóbal (2005)
Of the 2005, sarcòptica one of the September of first week of the month of of the the one of until of from half-full of the month of Julio of I make The present of the work of investigation of the demodècica and the scabies of the the one of by of the affected ones of owners of the animals of the respective ones of addresses of his of those of of Machala in of the city of the the one of in. Investigation of conformation of grups no considered the degree of infestaciòn, race, age, the scabies of the animals of of nor location of the injuries of sex. Son of the investigation of this paragraphs the raised ones of the objectives of: Dogs of those To identify the types of scabies in. Canine in the treatment of the scabies of the Doramectina and Amitraz of the effectiveness of the the one Determining. Canine of the evaluation the injuries in 8 of I determine of, the racially mixed one of and seven race bóxer one of race, a scabies ticó the diagnos them the examination of laboratory by means of of which of (demodècica, sarcòptica of and). Effect the one of Paragraphs the animals of group I (sarcòptica of the scabies) and an intramuscular dose of 200 ug/kg of alive weight (0,02 ml/kg) of in of the route by of Doramectina of administered them of animals of group II of (demodècica of the scabies) the applications of the six of In with between c/u of the days the one 8 of the interval. The one that of While the energetic ones of the baths those of animals of group III (sarcòptica of the scabies) and of group IV (demodècica of the scabies) of were applied to them of in of Amitraz with between with c/aplicación of the days the one 8 of the interval of the weeks the six of during of the sponge the one. Animal the one of # put under 2 of group II an application of the Doramectina of no had possibly of the satisfactory one and of the result I offer that the owner of the mascot no necessary one of the control the care and of gave him weighs an investigator the one of by of the given ones of the recommendations of. An end to improve of the state his the something of in of vitamin accepts paragraphs I apply of them the animals of those of all.